2015
DOI: 10.1188/15.onf.542-549
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress, Motor Abilities, and Behavioral Adjustment in Children Treated for Acute Lymphoblastic Leukemia

Abstract: Purpose/Objectives To examine associations among oxidative stress, fine and visual motor abilities, and behavioral adjustment in children receiving chemotherapy for acute lymphoblastic leukemia (ALL). Design A prospective repeated measures design was used. Serial cerebrospinal fluid (CSF) samples were collected during scheduled lumbar punctures. Setting Two pediatric oncology settings in the southwestern United States. Sample Eighty-nine children with ALL were followed from diagnosis to end of chemothera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…The majority of childhood cancer symptom research has been among heterogeneous groupings of pediatric oncology diagnoses (Hinds et al, 2007), which limits ability to tailor inventions for children, as specific diagnoses and treatment modalities are likely associated with associated with symptom severity and why significant variations occur even when disease and treatment are similar. Based on our prior work, we focused on the selectedThe potential influence of inflammatory and oxidative stress responses during the most intensive phase of childhood leukemia treatment that may influence symptom toxicities and should be explored (Caron et al, 2009;Hockenberry et al, 2014Hockenberry et al, , 2015Moore et al, 2015Moore et al, , 2018Rodgers et al, 2016;Stenzel et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of childhood cancer symptom research has been among heterogeneous groupings of pediatric oncology diagnoses (Hinds et al, 2007), which limits ability to tailor inventions for children, as specific diagnoses and treatment modalities are likely associated with associated with symptom severity and why significant variations occur even when disease and treatment are similar. Based on our prior work, we focused on the selectedThe potential influence of inflammatory and oxidative stress responses during the most intensive phase of childhood leukemia treatment that may influence symptom toxicities and should be explored (Caron et al, 2009;Hockenberry et al, 2014Hockenberry et al, , 2015Moore et al, 2015Moore et al, , 2018Rodgers et al, 2016;Stenzel et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding of the underlying mechanisms associated with symptom severity is limited; nor is it clear why significant variations in symptomology and severity occur across patients even when disease and treatment are similar. Based on our prior work, in the present study, we focused on selected inflammatory and oxidative stress responses during the most intensive phase of childhood leukemia treatment, which potentially influence symptom toxicities (Caron et al, 2009; Hockenberry et al, 2014, 2015; Moore et al, 2015, 2018; Rodgers et al, 2016; Stenzel et al, 2010).…”
mentioning
confidence: 99%
“…It was reported that children with ALL on maintenance therapy were potentially at risk for fine motor impairments 13 . Previous longitudinal studies assessing fine motor skills after approximately one year 4,9 and/or two years of treatment 10‐12 revealed conflicting results. A study conducted by Reinders‐Messelink et al 4 .…”
Section: Introductionmentioning
confidence: 99%
“…F I G U R E 1 Flow chart of patient recruitment tially at risk for fine motor impairments. 13 Previous longitudinal studies assessing fine motor skills after approximately one year 4,9 and/or two years of treatment [10][11][12] revealed conflicting results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation